Assessment of dysfunctional tunneled hemodialysis catheters and outcome of endovascular salvage techniques: a simple solution to a complex problem - Xu, Tao; Zeng, Ni; Li, Nan (Frontiers in Cardiovascular Medicine, 2023)
Objective The aim of this study was to evaluate the causes of the dysfunctional tunneled cuffed catheters (TCCs) using multi-spiral computed tomography venography (MSCTV), and to analyze the outcomes of endovascular salvage techniques. Material and methods This retrospective review data from 27 patients who experienced TCC dysfunction between July 1, 2016 and January 31, 2021 was conducted. Patients’ demographic data, clinical signs and symptoms, and imaging data were collected from interventional radiology database. Results MSCTV showed a range of abnormalities in the hemodialysis (HD) patients, including central venous occlusion (n = 4), fibrin sheath formation (n = 3), malposition of the catheter tips (n = 4), central venous perforation (n = 1), thrombus formation (n = 12), regular catheter exchange without determined lesions (n = 3). Interventional catheter salvage procedures were performed, such as catheter exchange, balloon disruption of a fibrin sheath, angioplasty for central vein stenosis, and stent deployment. The technical success rate for catheter insertions was 100%, and no procedure-related severe complications were observed. The 30-day catheter patency for all assessable catheters was 85.2%. Conclusion The use of MSCTV showed abnormal findings in almost 88.9% of cases concerning dysfunctional TCC. In this study, the examined appropriate endovascular techniques were found to be safe and technically successful, with a low incidence of procedure-related complications.